INTEGRASI NILAI-NILAI MODERASI BERAGAMA MELALUI PEMBELAJARAN PAI BERBASIS PROYEK (PROJECT BASED LEARNING) DI SDN 2 KRUI KECAMATAN PESISIR TENGAH KABUPATEN PESISIR BARAT LAMPUNG TAHUN AJARAN 2025/2026 - Afriani, Ayu Indria (UNISAN JURNAL, 2025)
This study aims to analyze the integration of religious moderation values through Project Based Learning (PjBL) in Islamic Religious Education at SDN 2 Krui, Pesisir Tengah District, Pesisir Barat Regency, Lampung, in the 2025/2026 academic year. Religious moderation is a crucial issue in elementary education because it shapes students’ character to become tolerant, peaceful, and appreciative of differences. Project Based Learning was selected as it provides hands-on learning experiences involving collaboration, problem-solving, and the practical application of values. This research employed a descriptive qualitative method with data collected through observations, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman model to identify patterns in how moderation values were integrated into PAI project activities. The findings indicate that Project Based Learning is effective in instilling religious moderation values such as tolerance, non-violence, dialogue, balanced understanding, and social cooperation. Students demonstrated behavioral improvements, including the ability to engage in healthy discussions, respect peers’ opinions, resolve conflicts peacefully, and collaborate harmoniously in groups. Teachers served as facilitators who connected religious moderation values with project activities, while the school principal provided structural and logistical support. The results suggest that integrating religious moderation within PjBL enhances students’ moderate religious attitudes and makes Islamic Education learning more meaningful and contextual. This model is recommended for wider implementation in elementary schools as a strategy to strengthen character education.